Impaired Function of the Calcium-Dependent Protein Kinase, OsCPK12, Leads to Early Senescence in Rice (Oryza sativa L.) - Wang, Beifang; Zhang, Yingxin; Bi, Zhenzhen; Liu, Qunen; Xu, Tingting; Yu, Ning; Cao, Yongrun; Zhu, Aike; Wu, Weixun; Zhan, Xiaodeng; Anis, Galal Bakr; Yu, Ping; et al. (Frontiers in Plant Science, 2019)
Premature leaf senescence affects plant yield and quality, and numerous researches about it have been conducted until now. In this study, we identified an early senescent mutant es4 in rice (Oryza sativa L.); early senescence appeared approximately at 60 dps and became increasingly senescent with the growth of es4 mutant. We detected that content of reactive oxygen species (ROS) and malonaldehyde (MDA), as well as activity of superoxide dismutase (SOD) were elevated, while chlorophyll content, soluble protein content, activity of catalase (CAT), activity of peroxidase (POD) and photosynthetic rate were reduced in the es4 mutant leaves. We mapped es4 in a 33.5Kb physical distance on chromosome 4 by map-based cloning. Sequencing analysis in target interval indicated there was an eight bases deletion mutation in OsCPK12 which encoded a calcium-dependent protein kinase. Functional complementation of OsCPK12 in es4 completely restored the normal phenotype. We used CRISPR/Cas9 for targeted disruption of OsCPK12 in ZH8015 and all the mutants exhibited the premature senescence. All the results indicated that the phenotype of es4 was caused by the mutation of OsCPK12. Overexpression of OsCPK12 in ZH8015 enhanced the net photosynthetic rate (Pn) and chlorophyll content. OsCPK12 was mainly expressed in green organs. The results of qRT-PCR analysis showed that the expression levels of some key genes involved in senescence, chlorophyll biosynthesis, and photosynthesis were significantly altered in the es4 mutant. Our results demonstrate that the mutant of OsCPK12 triggers the premature leaf senescence; however, the overexpression of OsCPK12 may delay its growth period and provide the potentially positive effect on productivity in rice.